2022
DOI: 10.31635/ccschem.021.202100919
|View full text |Cite
|
Sign up to set email alerts
|

Successive Free-Radical C(sp 2 )–C(sp 2 ) Coupling Reactions to Form Graphene

Abstract: Graphene has aroused great interest on account of its exciting properties and potential applications, but its production on a large-scale still presents considerable challenges. Here, we report the synthesis of predominately few-layer graphene, due to - stacking, as well as single-layer graphene, from reaction between hexabromobenzene and sodium metal, followed by annealing treatment to improve crystallinity.The reaction proceeds via a free-radical C(sp 2 )-C(sp 2 ) coupling mechanism, which is supported by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 51 publications
3
23
0
Order By: Relevance
“…Some short‐range ordering of the GBs is demonstrated by both X‐ray diffraction (Figure S3) and Raman spectroscopy (Figure 1f) and is consistent with what is typically seen in defective graphene. Following normalization processing, [5] the X‐ray photoelectron spectroscopy (XPS) data (Figure 1g) identified that the oxygen content of the GBs was 5.89 at.% (Figure 1g, Figure S4, and Tables S3 & S4). The fraction of sp 2 carbon relative to the total carbon was 82.8 at.%.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Some short‐range ordering of the GBs is demonstrated by both X‐ray diffraction (Figure S3) and Raman spectroscopy (Figure 1f) and is consistent with what is typically seen in defective graphene. Following normalization processing, [5] the X‐ray photoelectron spectroscopy (XPS) data (Figure 1g) identified that the oxygen content of the GBs was 5.89 at.% (Figure 1g, Figure S4, and Tables S3 & S4). The fraction of sp 2 carbon relative to the total carbon was 82.8 at.%.…”
Section: Resultsmentioning
confidence: 99%
“…The fitting results of the C1s signal showed that the concentration of C−H bonds was 16.5 at.%, which is consistent with the proton hyperfine coupling effects observed in the ESR data (see below). In the 13 C solid‐state nuclear magnetic resonance (ssNMR) spectrum (Figure 1h), the peaks at 128.03 ppm, and 140.75 ppm, identified by the cross‐polarization‐polarization inversion (CPPI) technique, belong to the hydrogen‐bonded aromatic carbons and carbon‐attached aromatic carbons, respectively (Figure S5), [13] while the 1 H ssNMR characterization showed that two types of protons were found in the product (Figure 1i and Figure S6); these correspond to aromatic hydrogens ( δ =6.86 ppm), and those from shielded hydroxyl hydrogens ( δ =1.57 ppm), respectively [5] …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations